A questionnaire to measure the quality of midwifery care in the postpartum period from women's point of view: development and psychometric testing of MMAYpostpartum - Mirjam Peters; Petra Kolip; Rainhild Schäfers (BMC, 2021)
Abstract Background Home postpartum care is a major part of midwifery care in Germany. The user perspective plays an increasingly important role in the evaluation of health services, but there is a lack of valid and theoretically based measuring instruments, especially in midwifery care. The aim of this study was to develop and validate an instrument for measuring quality of midwifery care in the postpartum period from the perspective of women. Methods The following steps were taken to achieve this: (1) definition of the goals of midwifery work; (2) literature-based item development; (3) item selection based on a pre-test (n = 16); (4) item reduction and investigation of factor structure by means of explorative factor analysis (EFA; n = 133);(5) second EFA (n = 741) and confirmatory factor analysis (CFA; n = 744) based on a split representative sample survey; (6) hypothesis-based testing of correlations to sociodemographic characteristics of women and to characteristics of care. Results Measurement of Midwifery quality postpartum (MMAYpostpartum) consists of three scales with a total of 17 items which were found to have acceptable internal consistency: Personal Control (Cronbach's alpha = .80), Trusting Relationship (Cronbach's alpha = .87) and Orientation and Security (Cronbach's alpha = .78). CFA verified and confirmed three factors: CFI = .928, TLI = .914, RMSEA = 0.073. Conclusion MMAYpostpartum is a predominantly valid, reliable short tool for evaluating the quality of midwifery care postpartum. It can be used to evaluate midwifery care, to compare different care models and in intervention research. It thus supports the orientation of midwives' work towards the needs of women and their families.